2020
DOI: 10.4018/ijgbl.2020070101
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Digital Games in Second Language Learning Studies

Abstract: This systematic review presents a definition for digital games within the second/foreign language (L2) learning research field. This definition is used to identify games used in research in the last five years (2012-2017). Forty-nine studies were identified and then summarized by type of research, game genre employed, age, and size of sample populations, and focus of research (vocabulary acquisition, student perspectives, etc.). Next, the research is synthesized by the L2 aspects investigated in each study. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Degirmenci [31] stated that there will be times when learners will face difficulties using Quizizz due to various factors such as Internet connection and device availability. This is supported by Poole and Midura [39], Moakofhi et al [48], and Weng et al [52], who claimed that Internet connection hinders the maximum exploitation of various online platforms such as Quizizz. As mentioned earlier, this causes inequality in education, especially among poorer students.…”
Section: Teachers' Perspective On the Difficulty Of Using Quizizzmentioning
confidence: 76%
See 2 more Smart Citations
“…Degirmenci [31] stated that there will be times when learners will face difficulties using Quizizz due to various factors such as Internet connection and device availability. This is supported by Poole and Midura [39], Moakofhi et al [48], and Weng et al [52], who claimed that Internet connection hinders the maximum exploitation of various online platforms such as Quizizz. As mentioned earlier, this causes inequality in education, especially among poorer students.…”
Section: Teachers' Perspective On the Difficulty Of Using Quizizzmentioning
confidence: 76%
“…After the four phases of selecting the eligible articles for review, 45 were found to be suitable to be used in this systematic review due to the nature of the respective studies. From the articles, four main aspects of teachers' perspectives on the use of Quizizz could be seen, mainly, effectiveness , feasibility [14,15,19,20,22,23,26,27,31,36,38,41,[43][44][45][46][47][48], difficulty [16,17,19,26,28,31,39,41,43,46,[48][49][50][51][52], and motivation [14,17,[24][25][26]31,32,35,38,40,41,44,45,47,49,50,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a certain level or "rank" can be a reward for achieving a certain level of success. The learning process can utilize the character development pattern of a fantasy role-playing game (Hung et al, 2018;Poole and Clarke-Midura, 2020). As noted by the researchers, the means of gamification affect adults as effectively as they do children and adolescents (Hung et al, 2018;Poole and Clarke-Midura, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Due to their potential effects on L2 /FL learning, digital games have provided the inspiration for numerous studies in the last 30 years. Depending on this, the digital gamebased learning area has been growing rapidly (Cornillie, Clarebout, & Desmet, 2012;Hwang & Wu, 2012;Poole & Clarke-Midura, 2020). An important part of the studies carried out in this learning area focused on the investigation of the effect of digital games on vocabulary knowledge/ acquisition (Hung et al, 2018;Tsai & Tsai, 2018;Zhang, 2018).…”
Section: Introductionmentioning
confidence: 99%